Investigation on the tensile and flexural behavior of coconut inflorescence fiber reinforced unsaturated polyester resin composites. (27th January 2020) - Karthik, S; Arunachalam, V P
Abstract: Natural fibers as reinforcement with polymer matrix have gained more advantage owing to its low density, high specific properties, biodegradability and abundant availability. In this connection an investigation has been carried out to make use of a newly identified natural fiber named coconut inflorescence fiber to reinforce with polyester resin. The natural fiber after extraction is subjected to mercerization treatment and the effect of mercerization on the surface of CIF was studied by FTIR and XRD analysis. FTIR spectrum analysis revealed the removal of functional groups present in the natural fiber owing to mercerization of CIF. XRD analysis shows improvement in crystalline size and crystalline index of the CIF as a result of mercerization. Samples of CIF/polyester composites were prepared by varying the length of the fiber as 10, 30, 50, 70 and 100 mm to be reinforced with different volume fractions of fiber/polyester resin as 10, 15, 20, 25 and 30% respectively and the specimens were cut as per ASTM standards for testing. Further samples were taken for testing of tensile strength and flexural strength. Results showed fiber length played a predominant role for the increase in tensile and flexural strength of the composites for 25% volume fraction. SEM analysis was done to predict the effect of fracture behaviour of the composite specimen.